Exploring the role of district clinical specialist teams in maternal health outcomes in a South African district: A mixed method study from 2012 to 2020 - Basu, J; Stewart, A; Basu, D; Wing, J; Feucht, U (South African medical journal, 2024)
Background. High maternal and child mortality in South Africa (SA) necessitated the establishment of district clinical specialist teams (DCSTs) in all health districts in 2012, mandated to work in collaboration with district managers and health professionals to achieve joint goals of improved maternal and child health services and outcomes. Objectives. Within the context of SA district health services, to explore the various obstetric intervention measures undertaken by a DCST over an 8-year period (July 2012 - February 2020), as aligned to the national DCST policy framework, and to document the knowledge and perceptions among managers and health professionals on the work done by the DCST in the district health service. Methods. A review of DCST reports and documents was conducted along with in-person structured interviews among health professionals and district health managers in the Ekurhuleni Health District in SA. Health professionals who had a working relationship with the DCST and relevant managers of health, including CEOs, clinical managers, community health centre managers, maternal and child health co-ordinators and municipal managers were selected for the interview. Interviews were conducted by the interviewer using a data collection tool focused on the scope of work and acceptance of the DCST in improving maternal health services in a geographically defined district health system. Data collection tools were completed by the interviewer upon questioning the participants. Data were analysed by documenting the activities of the DCST, and thematic analysis was performed for the interviews. Results. Analysis of DCST reports and documents revealed the broad range of activities, including clinical training and mentoring, clinical work, supervision, audit, research, monitoring and evaluation and clinical risk management. Thematic analysis extracted seven themes, namely clinical effectiveness, clinical risk management, professional development, accountability for maternal and child health, clinical work, monitoring and evaluation, and leadership and governance. All (n=20) participants acknowledged the positive impact of the DCST on the improvement in maternal health services. Conclusion. The DCST was perceived by local peers as a successful strategy to improve maternal health services in a district health service. This success is likely rooted in its focused intervention measures, within a supportive environment of district managers and health professionals. Such district-based clinical teams are a potential strategy to improve maternal health services within primary healthcare services.